Kemampuan Produksi Rumput Panicum maximum cv Gatton pada Lahan Kering di Provinsi Lampung - Suretno, Nandari Dyah; Tambunan, Reny Debora; Novitasari, Erliana (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Suretno ND, Tambunan RD, Novitasari E. 2022. Production capability of panicum maximum cv gatton grass on dry land of Lampung Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 922-928. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The ability of forage plants to adapt differently to different types of soil. Soil type will affect the availability of groundwater, where groundwater is a limiting factor for plant growth. Limited groundwater causes drought stress in plants that disrupt plant growth and biomass production. Based on these differences in adaptability, this study aimed to determine the production capacity of Panicum maximum cv Gatton grass planted on dry land. The study was conducted at Natar Agricultural Science Park, South Lampung Regency, Lampung Province. The material used is Panicum maximum cv Gatton grass which was arranged in a completely randomized design with four replications. The planting distance of grass was 0.5 x 0.5 m2. Harvesting was performed when the grass was four months after planting, with five clumps per replication. The morphological character parameters measured included plant height, stem height, leaf length, leaf width, stem diameter, and the number of branches. Productivity parameters were seen based on the number of tillers and fresh clump weight. The results showed that for morphological parameters, as follows: the average plant height of Panicum maximum cv Gatton grass was 123.74 cm; stem height 90.65 cm; leaf length 26.64 cm; leaf width 1.46 cm; rod diameter 3.91 mm; and the number of branches 4.4. As for the productivity parameter, the average number of tillers was 42.15, with a fresh weight of grass per clump of 0.86 kg. It is concluded that Panicum maximum cv Gatton grass is a medium-type Bengal grass cultivar which has good production capability when planted on dry land.